2012
DOI: 10.1074/jbc.m111.308239
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Cyanobacterial Magnesium Chelatase H Subunit Determined by Single Particle Reconstruction and Small-angle X-ray Scattering

Abstract: Background:In chlorophyll biosynthesis, ChlH is the protoporphyrin-binding subunit of magnesium chelatase. Results: ChlH has an ϳ132-kDa domain with a cavity, connected to an ϳ16-kDa domain. Conclusion: ChlH could enclose the magnesium protoporphyrin product, chaperoning it to the next enzyme in the pathway. Significance: The structure of ChlH will help to unravel its multiple catalytic and regulatory functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…CHLH protein sequences are well conserved from photosynthetic bacteria to land plants. In addition, the protein structure of CHLH has been studied using single-particle reconstruction and small-angle X-ray scattering (Qian et al, 2012), and the crystal structure of Synechocystis PCC6803 CHLH (SynCHLH) was recently solved at 2.5 Å resolution (Chen et al, 2015). SynCHLH is thought to consist of six domains (I–VI, Supplementary Figures 1, 14), with small amino (N)-terminal domains (domains I and II) that form a “head” and “neck” structure, followed by a cage-like assembly (domains III-VI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHLH protein sequences are well conserved from photosynthetic bacteria to land plants. In addition, the protein structure of CHLH has been studied using single-particle reconstruction and small-angle X-ray scattering (Qian et al, 2012), and the crystal structure of Synechocystis PCC6803 CHLH (SynCHLH) was recently solved at 2.5 Å resolution (Chen et al, 2015). SynCHLH is thought to consist of six domains (I–VI, Supplementary Figures 1, 14), with small amino (N)-terminal domains (domains I and II) that form a “head” and “neck” structure, followed by a cage-like assembly (domains III-VI).…”
Section: Introductionmentioning
confidence: 99%
“…SynCHLH is thought to consist of six domains (I–VI, Supplementary Figures 1, 14), with small amino (N)-terminal domains (domains I and II) that form a “head” and “neck” structure, followed by a cage-like assembly (domains III-VI). It was reported that CHLH predominantly exists as a monomer in solution (Qian et al, 2012), whereas a loosely bound CHLH dimer was observed in the crystal. The dimerization interface are domains I and V, which is consistent with a previous study that removal of the N-terminal 159 residues of T. elongates ChlH facilitates a monomeric state (Adams et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Rather less is known about the H subunit, although a low-resolution structural model of BchH from Rba. capsulatus has been obtained through 3D reconstruction of negatively stained single particles [ 17 ], and a similar approach, augmented by SAXS, was used to determine a low resolution structure of the cyanobacterial ChlH subunit [ 18 ]. In contrast with the more open BchH structure, ChlH forms a more enclosed cage-like assembly, connected to an N-terminal ‘head’ region adjacent to a 5 nm-diameter opening in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the more open BchH structure, ChlH forms a more enclosed cage-like assembly, connected to an N-terminal ‘head’ region adjacent to a 5 nm-diameter opening in the structure. It was suggested that the more enclosed ChlH structure affords some protection for the labile MgProto product, given the potentially damaging combination of light and oxygen within cells of oxygenic phototrophs such as cyanobacteria and plants [ 18 ]. A more complex structure for the ChlH with respect to BchH could also be a consequence of interactions with the Gun4 protein [ 19 , 20 ], which stimulates Mg-chelatase at low magnesium concentrations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation